PERAN PEKERJA SOSIAL KOREKSIONAL DALAM REHABILITASI DAN REINTEGRASI SOSIAL ANAK BERHADAPAN DENGAN HUKUM DI LKSA BENGKEL JIWA KABUPATEN JEMBER - Atik Rahmawati; Wahyuni Mayangsari (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2022)
Children in Conflict with the Law (ABH) is one of the Social Welfare Service Needs (PPKS) which has the right to protection and the fulfillment of children's rights by the state. Law No. 11 of 2012 concerning the Juvenile Justice System, as well as Minister of Social Affairs Regulation (Permensos) No. 26 of 2018 concerning Social Rehabilitation and Reintegration for ABHs provides a breath of fresh air for the juvenile justice system in Indonesia, with a new breakthrough in diversion and the handling of children involving the community through the Child Welfare Institution (LKSA). ABH rehabilitation is no longer placed in prison and mixed with adult detainees, but is entrusted and integrated into activities managed by LKSA. LKSA Bengkel Jiwa in Jember Regency exists as an institution that oversees and implements a responsive justice system for children. Professional LKSA management involves the role of social workers in the correctional sector as mandated by the Child Protection Law no. 35 of 2014. This study was analyzed using a qualitative research approach by conducting in-depth interviews with social workers and administrators at LKSA Bengkel Jiwa, Jember Regency. The results of the study show that the role of social workers is important as the vanguard who provides assistance, contact, and face to face with ABH both during the judicial process in the police, judicial proceedings in court, after court decisions, and after undergoing detention.